Integrating Microcontroller Programming and 3D Design for Community-based Experiential Learning - Nova Eka Budiyanta; Hanugra Aulia Sidharta; Vivi Triyanti; Diah Risqiwati (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
This study presents a community based workshop designed to enhance digital literacy through hands-on learning that combines microcontroller programming and three-dimensional (3D) design. The activity adopted a Do It Yourself (DIY) approach to bridge theoretical understanding and practical skills. Participants, consisting of students and young learners, developed a functional digital clock using an Arduino based microcontroller and designed its custom 3D printed enclosure. A mixed-method evaluation was conducted to assess learning outcomes. Quantitative results from a post activity questionnaire showed a high satisfaction level, with an overall mean score of 3.41, categorized as very high across five learning aspects which are motivation, comprehension, facilitation, relevance, and reflective impact. Qualitative feedback supported these findings, indicating that participants gained confidence, curiosity, and a deeper understanding through direct experimentation and collaborative mentoring. The results confirm that short term, project based workshops can effectively improve digital competence and creative confidence in community settings. Integrating accessible hardware and affordable fabrication tools provides a scalable model for STEM oriented education. The initiative demonstrates how experiential learning can promote innovation, problem solving, and technological empowerment, offering a sustainable framework for future programs in digital literacy and maker based education.